Analisis Penerapan Strategi Manajemen Perubahan dan Kreativitas di Indonesia Pada Era Pandemi COVID-19 - Nasution, Amanda Damayanti; Aslami, Nuri (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
About Change Management is one of the changes in regulating business organizations which originates only from Planning, Organizing, Actuating and Controlling. If it is related to the sudden COVID-19 pandemic, change management becomes relevant because most business organizations inevitably have to be able to adapt to survive. This paper aims to describe management change and creativity in dealing with the COVID-19 pandemic. The facts reveal that there are social and economic inequalities in society, both individually and in groups. The author collects news, both from various journals and social media related to the relationship between leaders and subordinates. The results of this paper are expected to provide positive input about Change Management as a whole. This research was conducted to determine the business strategies applied by Micro, Small and Medium Enterprises (MSMEs) in the face of the COVID-19 pandemic. The object of research is the snack industry with the trademark Waroenk Ngemil which is located on Sadang street, Bandung Regency. The method used is a qualitative research method with a descriptive approach. Based on the research results, it was obtained data that the business strategy in marketing its products is through social media. From the results of the research above, it can be explained that this strategy can work as expected by paying attention to the purchasing power of consumers during the COVID-19 pandemic. However, by using social media facilities, the funds needed by small business actors have an impact on reducing business capital. From the description above, it can be concluded that the role of the government and banking is very important, especially with regard to training in the use of information technology so that small business products can survive the COVID-19 pandemic